2003
DOI: 10.1017/s0954579403000026
|View full text |Cite
|
Sign up to set email alerts
|

Child–parent attachment following early institutional deprivation

Abstract: Child–parent attachment quality with an adoptive caregiver at age 4 years was examined in a sample of 111 children adopted into the United Kingdom following early severe deprivation in Romania and a comparison group of 52 nondeprived within–United Kingdom adoptees. Findings indicated that, compared with nondeprived adoptees, children who experienced early severe deprivation were less likely to be securely attached and more likely to show atypical patterns of attachment behavior; ordinary forms of insecure atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
204
0
12

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(225 citation statements)
references
References 5 publications
9
204
0
12
Order By: Relevance
“…Measures of indiscriminate behavior clearly diverge from other measures of attachment quality, and in fact, indiscriminate behavior has been identified in children who lack and do not lack preferred attachment figures (Chisholm, 1998;O'Connor et al, 2003;Zeanah et al, 2005a). The disinhibited pattern also is far less responsive than is the inhibited pattern to enhanced caregiving (Zeanah et al, 2005a).…”
Section: Summary and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measures of indiscriminate behavior clearly diverge from other measures of attachment quality, and in fact, indiscriminate behavior has been identified in children who lack and do not lack preferred attachment figures (Chisholm, 1998;O'Connor et al, 2003;Zeanah et al, 2005a). The disinhibited pattern also is far less responsive than is the inhibited pattern to enhanced caregiving (Zeanah et al, 2005a).…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…The disinhibited pattern also is far less responsive than is the inhibited pattern to enhanced caregiving (Zeanah et al, 2005a). Perhaps most troubling is the finding that young children who appear to have established attachments, sometimes even secure ones to adoptive or foster parents, may demonstrate significant levels of indiscriminate behavior (Chisholm, 1998;O'Connor et al, 2003). This seems to suggest that indiscriminate behavior may represent something other than an attachment disorder.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…O'Connor's data suggested that even if a child has been socially deprived in early infancy, he or she is still capable of developing a form of attachment to his caregiver. However, O'Connor et al's (2003) study only confirmed that socially deprived children who are adopted before the age of two are capable of forming attachments to their adoptive parents. It is therefore inconclusive in proving the impact that age has on a child's ability to form an attachment to his or her adoptive parents.…”
Section: "The Greatest Terror a Child Can Have Is That He Is Not Lovementioning
confidence: 83%
“…When a child is socially deprived, he or she is denied the appropriate amount of attention from a responsive caregiver. In turn, the cycle a secure child has with his parent, known as the "need-arousalgratification-relief-need," cannot exist if the child is socially deprived (O'Connor, Marvin, Rutter, Olrick, & Britner, 2003;Cole, et al, 2005). Social deprivation is characterized by two components; social and emotional neglect (Tharp-Taylor, 2003).…”
Section: "The Greatest Terror a Child Can Have Is That He Is Not Lovementioning
confidence: 99%
“…В одних из них [15] при изменении со-циальной ситуации в положительную сторону имело ме-сто значительное улучшение состояния детей. Однако у детей с диагнозом расторможенного расстройства привя-занности этого установлено не было [16,17], и умеренно стабильные признаки этого синдрома нередко обнаружи-вались даже в школьном возрасте, несмотря на то, что де-ти жили в семье с должным уровнем заботы.…”
unclassified